Assessing the Potential of Parkia biglobosa (Jacq.) R.Br. ex. G. Don - A Leguminous Plant Species commonly found in Nigeria to Decontaminate Crude Oil-polluted Soil in Terrestrial Ecosystem - A. A. Oyedeji; O. F. Oyedeji; O. M. Immanuel; O. O. Adekoya (Journal of Applied Sciences and Environmental Management, 2024)
The potentials of Parkia biglobosa (a leguminous plant species) to decontaminated crude oil-polluted soil in terrestrial ecosystem was evaluated in this study using appropriate standard techniques to estimate seedling germination, height, collar diameter, number of leaves and physicochemical characteristics (organic matter, pH, calcium, magnesium and sodium, nitrogen, phosphorous and potassium) of soil used, were determined using standard protocols. Results indicated that varying concentration of crude oil influenced the variables measured. For 0 ml, 25 ml, 50 ml, 75 ml and 100 ml crude oil treatments, Parkia biglobosa had 18%, 18%, 16%, 13% and 11% germination rate correspondingly; mean height of 38.70cm, 26.80cm, 21.20cm, 18.50cm and 6.80cm respectively, mean collar diameter of 0.32mm, 0.30mm, 0.26mm, 0.24mm and 0.22mm respectively; 2, 0, 0, 0 and 0 nodules count respectively, and 8.00, 6.00, 5.00, 5.00 and 2.00 leaf count respectively. All physicochemical parameters measured decreased in the soil in inverse proportion to crude oil concentration. So also, seedling germination, height, collar diameter, number of leaves and nodulation decreased in inverse proportion to crude oil concentration. Parkia biglobosa grew tolerably in both high and low concentrations of crude oil, which is an indication of its able to withstand crude oil toxicity. Parkia biglobosa as a nitrogen fixing plant would be a good candidate for the terrestrial restoration of crude oil contaminated regions in Nigerian.